Exacerbation of autoimmune neuroinflammation by dietary sodium is genetically controlled and sex specific. Issue 8 (10th November 2017) - Krementsov, Dimitry N.; Case, Laure K.; Hickey, William F.; Teuscher, Cory
Abstract : Multiple sclerosis (MS) is a debilitating autoimmune neuroinflammatory disease influenced by genetics and the environment. MS incidence in female subjects has approximately tripled in the last century, suggesting a sex‐specific environmental influence. Recent animal and human studies have implicated dietary sodium as a risk factor in MS, whereby high sodium augmented the generation of T helper (Th ) 17 cells and exacerbated experimental autoimmune encephalomyelitis (EAE), the principal model of MS. However, whether dietary sodium interacts with sex or genetics remains unknown. Here, we show that high dietary sodium exacerbates EAE in a strain‐ and sex‐specific fashion. In C57BL6/J mice, exposure to a high‐salt diet exacerbated disease in both sexes, while in SJL/JCrHsd mice, it did so only in females. In further support of a genetic component, we found that sodium failed to modify EAE course in C57BL6/J mice carrying a 129/Sv‐derived interval on chromosome 17. Furthermore, we found that the high‐sodium diet did not augment Th17 or Th1 responses, but it did result in increased blood‐brain barrier permeability and brain pathology. Our results demonstrate that the effects of dietary sodium on autoimmune neuroinflammation are sex specific, genetically controlled, and CNS mediated.—Krementsov, D.N., Case, L.K., Hickey, W. F., Teuscher, C. Exacerbation of autoimmune neuroinflammation by dietary sodium is genetically controlled and sex specific. FASEB J. 29, 3446‐3457 (2015). www.fasebj.org